STEPPED APPLICATION OF EUBIOTICS IN TREATMENT OF PHLEGMONS OF THE MAXILLOFACIAL REGION IN COMBINATION WITH INTESTINAL DYSBIOSIS - Musurmanov , Fazliddin; Pulatova , Barno (Medical science of Uzbekistan, 2024)
Until now, more than 40% of beds in dental hospitals are occupied by patients with inflammatory processes in the maxillofacial region. The increase in the number of slowly acting hyporeactive forms of inflammation in recent years leads to local and general complications of the body, which determines the relevance of studying the issues of prevention, diagnosis and treatment of inflammatory processes. Analysis of the literature data, allowing to judge the development of dysbiotic processes in phlegmon and metabolic syndrome, showed the need for detailed clinical studies on this issue. One of the leading components of the general drug treatment of inflammatory diseases of the maxillofacial region is the use of eubiotics. Meanwhile, a decrease in the therapeutic dose of eubiotics leads to the development of resistance of microorganisms to them and low efficiency of the treatment. In this regard, in the modern therapy of purulent-inflammatory diseases, not only the development of new antibacterial agents, but also the methods of their administration, remains an urgent problem. The aim of our study was to increase the effectiveness of treatment of patients with phlegmons of the maxillofacial region on the basis of stepwise eubiotic therapy. Materials and methods of research 41 patients were examined, the patients were divided into 2 groups. The stepwise application of the drug "Bifidum Bacterin" helps to reduce the contamination of the wound, the intensity and seeding rate of aerobic microorganisms in the wound is significantly reduced. Positive clinical and laboratory parameters in patients according to microbiological studies contributed to a reduction in hospitalization times.